2003
DOI: 10.1074/jbc.m307002200
|View full text |Cite
|
Sign up to set email alerts
|

Intradiabodies, Bispecific, Tetravalent Antibodies for the Simultaneous Functional Knockout of Two Cell Surface Receptors

Abstract: The specific and high affinity binding properties of intracellular antibodies (intrabodies), combined with their ability to be stably expressed in defined organelles, provides powerful tools with a wide range of applications in the field of functional genomics and gene therapy. Intrabodies have been used to specifically target intracellular proteins, manipulate biological processes, and contribute to the understanding of their functions as well as for the generation of phenotypic knockouts in vivo by surface d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 37 publications
(40 reference statements)
0
45
1
4
Order By: Relevance
“…Interference with the VEGF͞VEGF receptor system by means of retroviral expression of dominant-negative VEGF receptor variants (8), VEGF-neutralizing antibodies (9,10), or recombinant VEGF-neutralizing receptor variants (11,12), or interference with the Tie-2 receptor pathway by means of soluble dominant-negative receptors (13,14), intrabodies (15), or oligonucleotide-based strategies including RNA aptamers and RNA interference (16), resulted in reduced tumor growth and tumor vascularization. Several studies suggest that the VEGF receptor pathway and the Tie-2 pathway are independent mediators of in vivo angiogenesis, leading to the hypothesis that simultaneous interference with both pathways should result in additive effects on tumor growth (14,17). To date, no studies have reported the effect of simultaneous VEGF-R2͞Tie-2 antagonism in vivo.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Interference with the VEGF͞VEGF receptor system by means of retroviral expression of dominant-negative VEGF receptor variants (8), VEGF-neutralizing antibodies (9,10), or recombinant VEGF-neutralizing receptor variants (11,12), or interference with the Tie-2 receptor pathway by means of soluble dominant-negative receptors (13,14), intrabodies (15), or oligonucleotide-based strategies including RNA aptamers and RNA interference (16), resulted in reduced tumor growth and tumor vascularization. Several studies suggest that the VEGF receptor pathway and the Tie-2 pathway are independent mediators of in vivo angiogenesis, leading to the hypothesis that simultaneous interference with both pathways should result in additive effects on tumor growth (14,17). To date, no studies have reported the effect of simultaneous VEGF-R2͞Tie-2 antagonism in vivo.…”
mentioning
confidence: 97%
“…The assembly of intradiabody constructs, the generation of adenoviral plasmids by homologous recombination, and the generation of high titer viral stocks was done essentially as described in ref. 17.…”
Section: Assembly Of Intradiabody Constructs In Padtrackcmv and Genermentioning
confidence: 99%
See 3 more Smart Citations